Compressive Properties And Simulation Of Low Density Polyethylene Foams - Zakaria, Zunaida (2013)
This research was conducted to study the compression properties and simulation of low density polyethylene foam. Samples compounding was done using thermostatically controlled heated two roll mill and foamed using a compression moulding via a single stage foaming process at 175°C. The compounds were prepared by changing dicumyl peroxide (DCP) concentration (i.e. 0.25, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75 and 2.0 phr) to evaluate its effect on structure and mechanical properties. The prepared samples were characterized through density, cell morphology (i.e. cell size and cell wall thickness) and compression test. It was observed that the relative density increased with increasing DCP concentration and this subsequently decrease the cell size and increase the cell wall thickness. In compression test, results indicated that the elastic modulus increased with increasing DCP concentration. The compression deformation mechanisms were implemented by capturing the image and recording the real-time changes during compression test. The localized bending and buckling of the cell walls in elastic region, cells collapse in densification region and shear band were observed in the foam. The shear band with high density region was discovered in perpendicular to loading direction and it was contributed by cells collapse. The modelling and simulation part were successfully performed using SolidWorks software package. For models that were constructed with the assistance of experimental results, the larger cell model experienced high displacement and low von Mises stress.